Company Value in the SRI-KEHATI Index: ESG Disclosure, Environmental Costs, and Company Size - Maulida, Triky Noor; Hadi, Abdul; Sudirwo (Jurnal Mebis, 2025)
The value of the company is an important factor in investment decisions. This study examines and analyzes the influence of ESG disclosure, environmental costs, and company size on company value in the SRI-KEHATI Index for 2020-2023 using Tobin’s Q as an indicator of company value. The population in this study includes companies listed on the SRI-KEHATI Index for 2020-2023. The research sample was selected using purposive sampling techniques, resulting in 12 companies. Data analysis was conducted using multiple linear regression analysis with the help of the IBM SPSS version 26 statistical application. The study concludes that only environmental costs positively impact company value. These findings can serve as an evaluation for companies on how ESG reports are presented to be more transparent and relevant to investors. In addition, the findings on environmental costs indicate that investment in environmental aspects can contribute to value enhancement. Therefore, companies can allocate a larger budget to environmental policies to strengthen investor confidence and enhance business sustainability.